2011
DOI: 10.1128/aem.02976-10
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Response of Listeria monocytogenes during Adaptation to Growth on Lactate and Diacetate Includes Synergistic Changes That Increase Fermentative Acetoin Production

Abstract: The organic acids lactate and diacetate are commonly used in combination in ready-to-eat foods because they show synergistic ability to inhibit the growth of Listeria monocytogenes. Full-genome microarrays were used to investigate the synergistic transcriptomic responses of two L. monocytogenes strains, H7858 (serotype 4b) and F6854 (serotype 1/2a), to these two organic acids under conditions representing osmotic and cold stress encountered in foods. Strains were exposed to brain heart infusion (BHI) broth at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 67 publications
3
32
1
Order By: Relevance
“…The production of acetate and propionate as by-products of ethanolamine and 1,2-propanediol degradation suggests that growth inhibitors that include these two organic acids may be able to more effectively inhibit L. monocytogenes growth than currently used growth inhibitors. This is supported by a recent transcriptomic study in BHIB-grown L. monocytogenes (17), which showed that exposure of L. monocytogenes to acetate and lactate led to decreased expression of lactate-and acetate-creating energy pathways, shifting ATP production to a less efficient pathway with acetoin, a noncharged molecule, as an end product.…”
Section: Figsupporting
confidence: 56%
See 2 more Smart Citations
“…The production of acetate and propionate as by-products of ethanolamine and 1,2-propanediol degradation suggests that growth inhibitors that include these two organic acids may be able to more effectively inhibit L. monocytogenes growth than currently used growth inhibitors. This is supported by a recent transcriptomic study in BHIB-grown L. monocytogenes (17), which showed that exposure of L. monocytogenes to acetate and lactate led to decreased expression of lactate-and acetate-creating energy pathways, shifting ATP production to a less efficient pathway with acetoin, a noncharged molecule, as an end product.…”
Section: Figsupporting
confidence: 56%
“…A number of previous studies have analyzed the transcriptomes of foodborne pathogens under stress conditions commonly present on/in food matrices (including hyperosmotic stress, cold stress, hydrostatic pressure stress, antimicrobial stress, acid stress, and alkali stress), using laboratory media modified to simulate these conditions as a model (15)(16)(17)(18)(19)(20)(21)(22)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These laboratory media include BHI broth (18,20,21,59), BHI agar (19), Luria-Bertani broth (60,61), tryptic soy broth (62), M9-glucose (63), and Listeria minimal medium (22) as reference conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this potential cross-protective effect has not been assessed for other relevant food antimicrobial compounds. Further, the evidence of VirR regulon induction under acid stress prompted us to hypothesize that a potential cross-protective effect would be VirR mediated (43)(44)(45). Our results indicated that exposure to 2% PL increased subsequent NIS and EPL resistance of both the parent strain and the ⌬virR mutant.…”
Section: Figmentioning
confidence: 49%
“…In contrast, there have been reports of a cross-protective phenomenon, where prior exposure to a stress may increase resistance against a subsequent stress (20, 42). Additionally, acid-induced transcriptome profiling in L. monocytogenes has suggested upregulation of stress-and virulence-related genes, including the VirR regulon, as part of acid stress adaptation (43)(44)(45). To test the hypothesis that prior exposure to organic acids induces crossprotection against the selected antimicrobials and is mediated by VirR, we exposed the L. monocytogenes parent strain and H7858 ⌬virR to BHI (no acid control), 2% PL, and 0.14% SD, followed by subsequent challenge with antimicrobial compounds.…”
Section: Preexposure To Organic Acids Induces Cross-protection In Anmentioning
confidence: 99%